Conversion to complete resection with mFOLFOX6 with bevacizumab or cetuximab based on K‐ras status for unresectable colorectal liver metastasis (BECK study). (29th April 2015) - Hatano, Etsuro; Okuno, Masayuki; Nakamura, Kojiro; Ishii, Takamichi; Seo, Satoru; Taura, Kojiro; Yasuchika, Kentaro; Yazawa, Takefumi; Zaima, Masazumi; Kanazawa, Akiyoshi; Terajima, Hiroaki; Kaihara, Satoshi; et al.
Abstract Background Patients with colorectal liver metastasis (CRLM) might be down‐staged by chemotherapy from an initially unresectable stage to a resectable stage. Because the tumor response to preoperative chemotherapy has been correlated with resection rate, the improved efficacy from the concept that only the patients without K‐ras mutations receive an anti‐EGFR antibody might be expected to increase the conversion rate. The purpose of this study is to evaluate the conversion rate from unresectable CRLM to complete resection. Methods We conducted a multi‐institutional phase II trial for unresectable CRLM. Patients received mFOLFOX6 with either bevacizumab (bev) or cetuximab (cet) based on K‐ras status (UMIN000004310). Planned treatment was for six cycles during which tumors were assessed for resectability every three cycles. Patients whose disease was unresectable after six cycles switched their chemotherapy regimen from mFOLFOX6 to FOLFIRI. The primary endpoint was R0 resection rate. Results Thirty‐five patients with unresectable CRLM were enrolled. A total of 22/12 patients with K‐ras wild‐type/mutant (wt/mt) were treated with mFOLFOX6 plus cet/bev, respectively. The overall response rate was 64.7% (wt/mt; 77.3%/41.7%, P = 0.04). In 20 patients (58.8%), hepatectomy was performed according to protocol treatment, and the conversion rate was 72.7%/33.3% in wt/mt patients, respectively (P = 0.03). Finally, 23 patients (67.6%) underwent hepatectomy, and the conversion rate was 77.2%/50.0% in wt/mt patients (P = 0.09). The overall R0 resection rate was 47.1% (wt/mt; 50.0%/41.7%, P = 0.36). Conclusions This prospective study showed that combined chemotherapy based on K‐ras status can facilitate conversion to resection in patients with unresectable CRLM.